From COVID-19 Personal Protective Equipment (PPE) to pollutants: A multi-analytical approach towards environmental weathering of gloves and face masks in beach sand and sea - Siebe Lievens; Lucia Ricci; Géraldine Dumont; Stefano Pezzini; Simona Bronco; Cristina De Monte; Jan Jordens; Aline Reis De Carvalho; Marina Locritani; Milica Velimirovic; Silvia Merlino (Marine Pollution Bulletin, 2025)

Italian Pellets Watch: First step towards national assessment of resin pellets distribution, characterization and pollutants absorption - Roberta Giugliano; Claudio Casani; Marina Locritani; Vincenzo Palleschi; Francesco Poggialini; Bruno Cocciaro; Lucia Ricci; Simona Bronco; Cristina De Monte; Leonardo Arrighetti; Barbara Vivaldi; Stefania Di Vito; et al. (Environmental Research, 2025)

Antidepressants and cardiovascular outcomes in patients without known cardiovascular risk - Simona Monte; Alejandro Macchia; Marilena Romero; Antonio D’Ettorre; Rachele Giuliani; Gianni Tognoni (European Journal of Clinical Pharmacology, 2009)

Omega-3 fatty acid supplementation reduces one-year risk of atrial fibrillation in patients hospitalized with myocardial infarction - Alejandro Macchia; Simona Monte; Fabio Pellegrini; Marilena Romero; Daniel Ferrante; Hernán Doval; Antonio D’Ettorre; Aldo Pietro Maggioni; Gianni Tognoni (European Journal of Clinical Pharmacology, 2008)

Nitrous oxide and methane fluxes from soils of the Orinoco savanna under different land uses - Castaldi Simona; De Pascale Raffaele Ariangelo; Grace John; Nikonova Nina; Montes Ruben; San José José (Global Change Biology, 2004)
The study investigates the effect of land‐use change on nitrous oxide (N 2 O) and methane (CH 4 ) fluxes from soil, in savanna ecosystems of the Orinoco region (Venezuela). Gas fluxes were measured by closed static chambers, in the wet and dry season, in representative systems of land management of the region: a cultivated pasture, an herbaceous savanna, a tree savanna and a woodland (control site). Higher N 2 O emissions were observed in the cultivated pasture and in the herbaceous savanna compared with the tree savanna and the woodland, and differences were mainly related to fine soil particle content and soil volumetric water content measured in the studied sites. Overall N 2 O emissions were quite low in all sites (0–1.58 mg N 2 O‐N m −2 day −1 ). The cultivated pasture and the woodland savanna were on average weak CH 4 sinks (−0.05±0.07 and −0.08±0.05 mg CH 4 m −2 day −1 , respectively), whereas the herbaceous savanna and the tree savanna showed net CH 4 production (0.23±0.05 and 0.19±0.05 mg CH 4 m −2 day −1 , respectively). Variations of CH 4 fluxes were mainly driven by variation of soil water‐filled pore space (WFPS), and a shift from net CH 4 consumption to net CH 4 production was observed at around 30% WFPS. Overall, the data suggest that conversion of woodland savanna to managed landscape could alter both CH 4 and N 2 O fluxes; however, the magnitude of such variation depends on the soil characteristics and on the type of land management before conversion.